2020
DOI: 10.1002/eap.2066
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland sharing by cattle and bees: moderate grazing does not impair bee communities and resource availability

Abstract: Rangelands are a dominant anthropogenic land use and a main driver of natural habitat loss worldwide. Land sharing, the integration of agricultural production and biodiversity conservation, may provide a platform for managing rangelands to fulfill multiple ecosystem services. However, livestock grazing can greatly affect biodiversity and little is known about its effects on providers of focal ecosystem services, such as pollinators. We investigated the effect of cattle grazing on bee communities and their fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
(137 reference statements)
0
10
1
Order By: Relevance
“…communities in a semi-arid prairie system in Oregon (USA), and showed that cattle presence caused soil compaction and a reduction in herbaceous litter. In contrast, tests of cattle-mediated effects on bee communities in arid Mediterranean habitats reported null effects on wild bee abundance and richness, despite impacts on forb communities and bee foraging preferences (Shapira et al, 2019).…”
Section: Effects Of Grazing Across Pollinator Life Historiesmentioning
confidence: 96%
“…communities in a semi-arid prairie system in Oregon (USA), and showed that cattle presence caused soil compaction and a reduction in herbaceous litter. In contrast, tests of cattle-mediated effects on bee communities in arid Mediterranean habitats reported null effects on wild bee abundance and richness, despite impacts on forb communities and bee foraging preferences (Shapira et al, 2019).…”
Section: Effects Of Grazing Across Pollinator Life Historiesmentioning
confidence: 96%
“…Cattle grazing is often reported to be disruptive to floral resource availability (Kimoto et al, 2012), but patchburn grazing helps to concentrate cattle in recently burned areas (Spiess et al, 2020), creating the necessary heterogeneity to support diverse pollinator communities (Kimoto et al, 2012;Hanberry et al, 2021;Samways et al, 2020). Our treatments likely needed additional time to develop, but they are predicted to increase land sharing between pollinators and livestock, similar to rangelands in Israel (Shapira et al, 2020).…”
Section: Pollinator Responses To Managementmentioning
confidence: 99%
“…Land sharing-management to benefit multiple ecosystem services-will be necessary as the amount of high-functioning native landscapes decreases due to erosion or urbanization (Cole et al, 2017;Öckinger & Smith, 2007;Sieverding et al, 2020). Instead of confining livestock production to rangelands and pollinator conservation to conservations lands (CRP, wildlife refuges), both efforts can be management goals in rangelands (Polasky et al, 2005;Senapathi et al, 2015;Shapira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted on the effects of livestock grazing on plants, from the individual to community level (Herrero-Juregui and Oesterheld, 2018). However, the cascading plant-mediated effects of grazing on higher trophic levels have been less studied, especially the effects on herbivorous ecosystem service providers, which rely on, or are directly affected by, plant communities (Shapira et al, 2020). Management and livestock pressure intensity in pastures are expected to have an important effect on the vegetation and consequently on ower-visiting insects, through a modi cation of the abiotic conditions and of the overall availability, quality, and phenology of pollinators' oral and nesting resources in the landscape (van Klink et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have found negative effects of increased grazing on insect pollinators due to decreased ower diversity and altered plant species composition (Kruess and Tscharntke, 2002;Minckley, 2014;Sjödin et al, 2008;Tadey, 2015), while others have shown instead positive impacts of increased grazing intensity compared to low or no-grazing sites (Carvell, 2002;Öckinger et al, 2006;van Klink et al, 2016). In the Mediterranean region, the few existing studies have shown that intermediate levels of grazing favored either pollinator abundance and richness or pollinator foraging resources (Lázaro et al, 2016;Shapira et al, 2020). Discrepancies among studies are likely the result of differences in habitat types and land-use histories, grazing level, and additional interacting management practices.…”
Section: Introductionmentioning
confidence: 99%